Álgebra e formação docente: uma análise dos projetos pedagógicos de curso de Licenciatura em Matemática do RS - Dias, Guédulla de Senna (2022)
This qualitative bibliographical research aimed to analyze the Course Pedagogical Process (CPP) of six Federal Universities (FU) in the state of Rio Grande do Sul (RS), Brazil, focusing on the pre-service education of Mathematic teachers regarding Algebra knowledge and the relations with school Algebra and Algebraic thinking. During the documental analysis of the CPP of the six FUs in RS, two analytical categories emerged: Algebra Knowledge treated/emphasized in the CPP of the researched institution, in which we tried to identify approximations and distances between academic Algebra and school Algebra; Aspects/Content of school Algebra and Algebraic thinking emphasized in other subjects of the degree. Regarding the first category, we highlight that, out of the 34 required subjects related to Academic Algebra, in 31 the focus is on studying and mastering specific concepts connected to academic Algebra. On the other three, we found evidence of some relation between the concepts studied and K-12 teaching. We identified in the CPP 10 optional subjects, amongst which Linear Algebra II was common to all. Based on the analysis of the six undergraduate courses, we can infer that the teacher education process values the study/acquisition of algebraic knowledge that constructs an advanced concept of school Mathematics, mainly school Algebra. Concerning the approximations and distances, we have perceived that the subjects in all degrees have certain similarities in Algebra knowledge and/or indicated references, and part of this knowledge is closer to the algebraic concepts used in K-12 education. However, most subjects (31) seem to prioritize academic Algebra aspects, distancing themselves from school Algebra. As for the second category, the knowledge related to school Algebra and/or Algebraic thinking are mainly proposed in subjects where some hours are allocated to Practice as a Curriculum Component (PCC). Therefore, we point out the need for the analyzed degrees to value a more questioning relationship between academic and school Algebra, guided by Algebra teaching in K-12 education, to enable teachers' training to work with the specificities of teaching and learning in this field of school Mathematics.